Reply to "Remarks on bank competition and convergence dynamics" - Maria Karadima; Helen Louri (Journal of Risk and Financial Management, 2020)
In this reply, we provide detailed answers to the remarks made by Tsionas on the use of stochastic frontier-based measures of market power in a part of our empirical study, which examines the fragmentation and convergence dynamics of market power, concentration and credit risk in the euro area banking sector during 2005-2017. Our answers clarify all the issues raised by Tsionas and show that the only challenging, in our opinion, point of the criticism has been based on a hypothesis that does not hold in the case of our study.
Keywords: 330; Lerner index; stochastic frontiers; convergence analysis